"Eleven vowels of Imilike Igbo including ATR and RTR schwa " (2024)
"In this paper, we examine the acoustics of vowels in the Imilike [-m-l-ke$] dialect of Igbo (Igboid, Niger-Congo), which has not previously been done. While Standard Igbo has eight vowels, previous auditorily-based research has identified eleven vowels in Imilike. Like Standard Igbo, Imilike contrasts vowels in Advanced/Retracted Tongue Root (ATR vs. RTR). We find that there are eleven vowels, distinguished most reliably by F1, B1, energy (dB) of voiced sound below 500Hz and duration. The results of this study also suggest that RTR vowels in Imilike might involve the laryngeal constriction and movement that accompany pharyngealization. The ATR and RTR schwas have similar phonological distribution and acoustic patterns as the other ATR and RTR vowels in the language.